Language learning motivation among Malaysian pre-university students - Muftah, Muneera; Rafik-Galea, Shameem (Canadian Center of Science and Education, 2013)
The study describes and examines Malaysian pre-university students' integrative and instrumental motivation toward learning English language. In this study, 182 non-English major students in one of the Malaysian public universities are selected to fill out a questionnaire reflecting their attitudes and motivation towards learning English. The findings indicate that Malaysian pre-university students have very high motivation and positive attitudes towards leaning English and that they are more instrumentally motivated. Based on the findings some suggestions and recommendations for teachers have been highlighted.